Cyclopia, Arhinia and Hermaphroditism Report in a Saanen Kid - Karan, Meryem; Ustundag, Yasemin; Aydin, Muhterem (Kafkas Univ, Veteriner Fakultesi Dergisi, 2011)
In this case, congenital anomalies belongs to a Saanen breed goat which gives her third birth have been investigated morphologically. Apart from the lack of the full fledge, it was not observed a significant anomaly in the inspection of abdomen. In situ locations of the skull and their fetaures differed greatly in the animal which possessed cyclopia and arhinia. In dissection of internal organs, apart from the organs existing in cavum pelvis, any defect were not observed.
Saanen irki bir o?lakta rastlanilan cyclopia, arhinia ve hermafroditizm olgusu
Keywords: Arhinia; Cyclopia; Hermaphroditism; Saanen goat